Investigating the Appropriateness and Validity of the Academic Motivation Scale-College Version for South African First-Year University Students (Journal of Student Affairs in Africa, 2021)
South African universities have one of the lowest graduation rates in the world, especially amongstfirst-year university students. South Africa's first-year university students are taxed with tremendouschallenges. One of the most important amongst these challenges is considered to be academic motivation, which is strongly related to students' academic success. Despite this, to date, little work hasbeen undertaken to source and validate a reliable instrument to measure students' academic motivation. This article is based on the proposition that there is a pressing need for a valid and reliable instrumentthat measures academic motivation and its effect on students' academic success. The psychometricproperties of the Academic Motivation Scale-College version were examined for first-year university students. The findings are promising for using this scale to measure academic motivation of first-yearuniversity students.
Keywords: Academic Motivation Scale-College version; convergent validity; criterion validity; discriminant validity; factorial validity; first-year university students; reliability